Inclusive Communities: A missional approach to racial inclusivity within the Dutch Reformed Church - Rossouw, Pieter Fourie (Stellenbosch Theological Journal, 2016)
This article dealt with racial diversity in homogenous white Afrikaans faith communities such as the Dutch Reformed Church (DRC). This study was partially an account of the researcher’s own discontent with being a minister in the DRC against the backdrop of his own journey of finding a racially integrated identity in a post-apartheid South Africa. It focused on the question of how a church like the DRC can play an intentional role in the formation of racially inclusive communities. The study brought together shifts in missional theology, personal reflections from DRC ministers and contemporary studies on whiteness. The researcher looked towards a missional imaginary as a field map for racial diversity in the church. This was mirrored against contemporary studies on white identity in a post-apartheid South Africa. From this conversation the researcher argued for a creative discovery of hybrid identities within white faith communities. Missional exercises such as listening to the stories of strangers, cross cultural pilgrimages and eating together in strange places can assist congregations on this journey.